2005
DOI: 10.1097/01.don.0000152298.81097.b7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evaluation of the Apical Seal in Roots Filled with a Polycaprolactone-Based Root Canal Filling Material

Abstract: This in vitro study compared the ultrastructural quality of the apical seal achieved with Resilon/Epiphany and gutta-percha/AH Plus. Single-rooted extracted human teeth were prepared using a crown-down technique, debrided with NaOCl and EDTA, and obturated with either Resilon/Epiphany or gutta-percha/AH Plus. They were examined for gaps along canal walls using SEM, and for apical leakage using a transmission electron microscopy (TEM). SEM revealed both gap-free regions, and gap-containing regions in canals fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
155
1
14

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(183 citation statements)
references
References 24 publications
13
155
1
14
Order By: Relevance
“…Epiphany has presented lower bond strength, even with the use of EDTA, which could play an important role with this sealer because of its self-etching characteristic and the hybrid layer formation that occurs in this kind of sealer. The removal of the smear layer created during instrumentation could lead to greater sealer penetration into the exposed tubules, which may increase adhesion 16) . The Epiphany composition is based on methacrylates (i.e., Ethoxylated bisphenol A dimethacrylate -BisEMA) and presents a dual cure polymerization system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epiphany has presented lower bond strength, even with the use of EDTA, which could play an important role with this sealer because of its self-etching characteristic and the hybrid layer formation that occurs in this kind of sealer. The removal of the smear layer created during instrumentation could lead to greater sealer penetration into the exposed tubules, which may increase adhesion 16) . The Epiphany composition is based on methacrylates (i.e., Ethoxylated bisphenol A dimethacrylate -BisEMA) and presents a dual cure polymerization system.…”
Section: Discussionmentioning
confidence: 99%
“…The teeth from all the groups were stored at 377C and 100% humidity for 7 days in order to allow the sealers to set 16) . Afterwards, the roots were sectioned on the long axis using a precision cutting machine (Isomet, Buehler Ltd., Lake Bluff, IL, USA) under constant water coolant.…”
Section: Push-out Testmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that a complete hermetic apical seal cannot be achieved with either of the two root canal filling materials. 69 In yet another study interfacial quality was compared between Epiphany and Epiphany SE and the surrounding dentin with conventional gutta-percha/AH plus root filling as reference for comparison. The results showed that nonbonding AH-plus/gutta-percha root fillings exhibited a significantly higher amount of gap-free regions and displayed significantly narrower gaps compared with the two adhesive root-filling groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to test the biological effects and to identify the components that cause these effects, e.g. dissolved components of the dental materials [7][8][9][10][11]. Thus biocompatibility testing should use solid specimens as well as extracts.…”
Section: Introductionmentioning
confidence: 99%